Application of the Dick and Carey Model in the Development of Yellow Book (Kitab Kuning) Reading Guidance Learning at Madrasah - Maula, Aris Rohmatul; Hamdani, Asep Saepul; Soraya, Irma (Yayasan Rahmat Islamiyah, 2025)
As a result of the influence of modernism, there is a shift in emphasis in the learning of yellow books (kitab kuning) in Islamic educational institutions, both in Islamic boarding schools and madrasas. Therefore, it is important for teachers of yellow book reading in madrasas to design learning development in order to meet learning objectives so as to create meaningful learning. The purpose of this study is to determine the application of the Dick and Carey model in the development of Yellow Book Reading Guidance learning at MTs Tarbiyatut Tholabah Lamongan. A qualitative case study approach was used in this study, with the data sources used consisting of primary data sources extracted from the process of observation, interviews and documentation. The results of this study state that the development of learning carried out by teachers of reading yellow books at MTs Tarbiyatut Tholabah class VII F is the development of teaching modules that use the steps of implementing the Dick and Carey model, namely: 1) Identifying general learning objectives, 2) Analyzing instruction, 3) Identifying initial abilities and characteristics of students, 4) Formulating specific learning objectives, 5) Developing assessment instruments, 6) Developing teaching strategies, 7) Developing and selecting teaching materials, 8) Formative evaluation, 9) Revising learning, 10) Summative evaluation.